Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1136/bmjopen-2014-006378
|View full text |Cite
|
Sign up to set email alerts
|

A cross-sectional exploration of the clinical characteristics of disengaged (NEET) young people in primary mental healthcare

Abstract: ObjectiveYouth with mental health problems often have difficulties engaging in education and employment. In Australia, youth mental health services have been widely established with a key aim of improving role functioning; however, there is little knowledge of those who are not engaged in employment, education or training (NEET) and the factors which may influence this. This study aimed to examine NEET status and its correlates in a sample of such youth.DesignCross-sectional data from a longitudinal cohort stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
69
5
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 81 publications
(91 citation statements)
references
References 35 publications
11
69
5
6
Order By: Relevance
“…This is congruent with other studies of work and study outcomes in young people which has also identified gender, educational attainment, socioeconomic background, recent cannabis use and, as previously discussed, family history of schizophrenia or bipolar disorder (Benjet et al, 2012;O'Dea et al, 2014). Prior research specific to help-seeking young people also identified being male and recent cannabis use (O'Dea et al, 2014). In-particular the influence of cannabis use on functioning in young people is well reported and regardless of psychiatric status there is an association between frequent harmful use and higher emotional and behavioural problems (Sawyer et al, 2000), reduced educational attainment (Lynskey et al, 2003;Schuster et al, 2001) and vocational functioning (Hyggen, 2012;O'Dea et al, 2014;Ringel et al, 2007).…”
Section: Vocational Functioning Neurocognitive Outcomes and Associatsupporting
confidence: 78%
See 4 more Smart Citations
“…This is congruent with other studies of work and study outcomes in young people which has also identified gender, educational attainment, socioeconomic background, recent cannabis use and, as previously discussed, family history of schizophrenia or bipolar disorder (Benjet et al, 2012;O'Dea et al, 2014). Prior research specific to help-seeking young people also identified being male and recent cannabis use (O'Dea et al, 2014). In-particular the influence of cannabis use on functioning in young people is well reported and regardless of psychiatric status there is an association between frequent harmful use and higher emotional and behavioural problems (Sawyer et al, 2000), reduced educational attainment (Lynskey et al, 2003;Schuster et al, 2001) and vocational functioning (Hyggen, 2012;O'Dea et al, 2014;Ringel et al, 2007).…”
Section: Vocational Functioning Neurocognitive Outcomes and Associatsupporting
confidence: 78%
“…This is congruent with other studies of work and study outcomes in young people which has also identified gender, educational attainment, socioeconomic background, recent cannabis use and, as previously discussed, family history of schizophrenia or bipolar disorder (Benjet et al, 2012;O'Dea et al, 2014). Prior research specific to help-seeking young people also identified being male and recent cannabis use (O'Dea et al, 2014).…”
Section: Vocational Functioning Neurocognitive Outcomes and Associatsupporting
confidence: 74%
See 3 more Smart Citations